2001
DOI: 10.1159/000052596
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Renal Cell Apoptosis by Antibodies and Complement

Abstract: Renal diseases are in many cases associated with the presence of increased numbers of apoptotic cells in the kidney. Apoptosis has been proposed as an important mechanism involved in the resolution of a proliferative response. Furthermore, recent studies indicate its possible involvement in progression of renal disease, leading to sclerosis. Moreover, in an experimental model of acute mesangioproliferative glomerulonephritis in the rat, induced via antibodies directed to Thy-1, evidence was obtained for the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Proliferation and apoptosis play a pivotal role in a variety of biological processes, such as morphogenesis during the embryonic stage, cell selection during lymphoid development, tissue repair after injury, regression of inflammation, elimination of cells at risk of developing into a tumor and lymphocyte-mediated killing [19]. A balance of proliferation and apoptosis is essential for the tissue homeostasis [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proliferation and apoptosis play a pivotal role in a variety of biological processes, such as morphogenesis during the embryonic stage, cell selection during lymphoid development, tissue repair after injury, regression of inflammation, elimination of cells at risk of developing into a tumor and lymphocyte-mediated killing [19]. A balance of proliferation and apoptosis is essential for the tissue homeostasis [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Probably the most thoroughly characterized death receptor is the cell membrane receptor Fas (CD 95), a member of the TNF receptor family. Cross-linking of Fas, either via specific antibodies or via its specific ligand, activates a cascade reaction of caspases, which are responsible for induction of membrane alterations, breakdown of cellular constituents and DNA, and finally cell death [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Injury in anti-Thy-1.1 nephritis is caused directly by binding of administered antibody to Thy-1.1 on the mesangial cell surface, which results in complement-dependent cell death in which both necrosis and apoptosis are prominent. 29 The earliest phase is accompanied by a marked influx of ED1-positive cells. Substantial numbers of macrophages have already localized 1 hour after injection of OX7 and this is consistent with the very early glomerular expression of MCP-1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Bcl-2 binds to Bax to form a Bax/Bcl-2 polymer to inhibit the apoptotic process (33). High expression levels of Bcl-2 also maintain cell stability by inducing glutathione aggregation in the cell nucleus to reduce caspase activity (34). The results of the present study suggested that PUMA may inhibit GBC invasion at least partially by regulating the expression of Bax and Bcl-2.…”
Section: Discussionmentioning
confidence: 52%